Невеста трех женихов: [роман] / Галина Артемьева - Артемьева Галина Марковна (Лабиринты души, 2011)
Экземпляры: (20170705) / Инвентарный номер: 36058 / Цена: 127.40 / Сис.шифр: Р2 / Авт.знак: А 86 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6